The role of game-based learning in dermatology: a scoping review on patient education - Mettarikanon, Dichitchai; Eden, Chime; Tawanwongsri, Weeratian (Frontiers in Communication, 2025)
IntroductionGame-based learning (GBL) has gained attention as an innovative approach to patient education, offering interactive and engaging experiences that enhance learning and self-management. In dermatology—where visual recognition and adherence to treatment are particularly important—GBL may offer unique educational advantages.MethodsThis scoping review aimed to map the existing literature on the use of GBL in dermatology patient education and to identify gaps for future investigation. A comprehensive search was conducted across Scopus, Medical Literature Analysis and Retrieval System Online (MEDLINE), and Directory of Open Access Journals (DOAJ), following the Joanna Briggs Institute methodology and the PRISMA-ScR checklist. Eligible studies were peer-reviewed primary research articles, published in English between January 2005 and May 2025, and focused on game-based interventions designed to educate individuals with dermatologic conditions.ResultsEight studies met the inclusion criteria, addressing a range of conditions including melanoma, atopic dermatitis, cutaneous leishmaniasis, and sun-related skin damage. Interventions featured gamification, serious games, and augmented reality formats. Most studies reported improvements in knowledge, recognition accuracy, treatment adherence, and user satisfaction. However, only three were randomized controlled trials, and the use of validated outcome measures was inconsistent. Digital usability testing was limited, and the majority of the game-based tools were institution-developed and not publicly accessible.DiscussionGBL shows promise as an engaging and potentially effective method for educating dermatology patients, particularly for conditions that rely heavily on visual learning. Nevertheless, the current body of evidence remains preliminary. Many studies had small sample sizes, varied in methodological quality, and underrepresented older adults and individuals with limited digital literacy. Future research should focus on rigorous study designs, broader participant inclusion, and long-term evaluation to support the integration of GBL into routine dermatologic care.